Proviral Quasispecies Diversity Is Not Associated With Virologic Breakthrough or CD4+ T Cell Loss in HIV-1 Elite Controllers - de Azevedo, Suwellen S. D.; Côrtes, Fernanda H.; Delatorre, Edson; Ribeiro-Alves, Marcelo; Hoagland, Brenda; Grinsztejn, Beatriz; Veloso, Valdilea G.; Morgado, Mariza G.; Bello, Gonzalo (Frontiers in Microbiology, 2019)
Elite controllers (EC) are able to control HIV-1 replication to extremely low levels (<50 HIV-1 RNA copies/mL) in the absence of antiretroviral therapy. Some EC, however, experience CD4+ T cell loss and/or lose their ability to control HIV-1 over the course of infection. High levels of HIV-1 env proviral diversity, activated T cells and pro-inflammatory cytokines were described as useful baseline biomarkers to predict virologic and/or immunologic progression in EC. The aim of this study was to assess the importance of proviral diversity as a prognostic marker of virologic and/or immunologic progression in EC. To this end, we analyzed the plasma viremia, total cell-associated HIV DNA, T cells dynamics, CD8+T cell activation (CD38+HLA-DR+) and pro-inflammatory cytokines (IP-10, IL-18, RANTES, PDGF-AA, and CTACK) in EC with low (ECLD = 4) and high (ECHD = 6) HIV-1 env proviral diversity. None of ECLD and ECHD subjects displayed evidence of immunologic progression (decrease in absolute and percentage of CD4+ T cells) and only one ECHD subject presented virologic progression (≥2 consecutive viral loads measurements above the detection limit) 2-5 years after determination of proviral diversity. Despite differences in proviral genetic diversity, the ECLD and ECHD subgroups displayed comparable levels of cell-associated HIV DNA, activated CD8+ T cells and plasmatic inflammatory biomarkers. These results indicate that the genetic diversity of the HIV-1 proviral reservoir is not a surrogate marker of residual viral replication, immune activation or inflammation, nor an accurate biomarker for the prediction of virologic breakthrough or CD4+ T cells loss in EC.